PUBLIC HEARING SEBAGAI RUANG (SARANA) PARTISIPASI MASYARAKAT UNTUK MEWUJUDKAN PERATURAN DAERAH YANG DEMOKRATIS (Studi Penyusunan Raperda Kota Salatiga Tentang Penyelenggaraan Tertib Tuna Sosial) - Alfret; Rauta, Umbu; Setyorini, Heny (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Public hearing is one of the instruments for Local People's Representative Council (DPRD) of Salatiga City to absorb people's aspirations in the formation of local regulations. Networking and absorbing the aspirations of the community is important in the process of forming local regulations so they can answer the needs and solve the problems, because sociologically, local regulations must prioritize usability and usefulness. This Public Hearing was held in order to absorb the aspirations of the community regarding the Draft Regional Regulation on the Implementation of Social Order. The activity began with the presentation of the substance of the Draft Regional Regulation then continued with a direct question and answer session, also can access by Youtube even for those who have not had the opportunity to submit questions and suggestions can access the google form link that has been provided. This activity provide benefit where the DPRD as the people's representative can absorb the aspirations of the community as a whole.